2018
DOI: 10.1111/ejss.12568
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of bacterial communities in aBetula albosinensisforest

Abstract: Soil bacteria play a key role in nutrient cycling, but the mechanisms behind seasonal variation of bacterial communities in different types of soil remain unclear. In this study, the bacterial composition during four seasons and at four soil depths (0–10, 10–20, 20–40 and 40–60 cm) in a Betula albosinensis forest of the Qinling Mountains (southern Shaanxi Province, China) was investigated. Illumina 16S rRNA gene sequencing was used to analyse soil bacterial diversity and communities. The soil properties, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Therefore, any change in the microbial communities of soil can lead to changes in various biochemical processes, thus affecting the stability of degraded ecosystems in mining areas, while also playing a vital role in the efficiency of ecological restoration. Over the course of a year, soil microbes face considerable variation in seasonal environmental factors, including temperature and humidity levels (López-Mondéjar et al, 2015) and the availability of nutrients (Du et al, 2018;Wang et al, 2018). Hence, soil microorganisms are often contingent on dynamic seasonal change characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any change in the microbial communities of soil can lead to changes in various biochemical processes, thus affecting the stability of degraded ecosystems in mining areas, while also playing a vital role in the efficiency of ecological restoration. Over the course of a year, soil microbes face considerable variation in seasonal environmental factors, including temperature and humidity levels (López-Mondéjar et al, 2015) and the availability of nutrients (Du et al, 2018;Wang et al, 2018). Hence, soil microorganisms are often contingent on dynamic seasonal change characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In this culture, Desulfovibrionales were dominated by sequences affiliated to the genus Desulfovibrio , a genus within which certain species are known to produce TMA, ethanol, and acetate from choline fermentation [ 85 ]. A predominance of Bacteroidetes , Firmicutes , and Methanomassiliicoccales was also reported for an environmental sample, in this case, a birch forest soil in winter [ 86 ]. Apart from methanogenic Archaea , other Archaea represented a marginal fraction of the total prokaryotic diversity, accounting for 46.2% and 2.3% of total read sequences at T1 and T2, respectively, to less than 0.1% of total sequences after the second week of incubation ( Figure S3A,B ).…”
Section: Resultsmentioning
confidence: 58%
“…The reality of global warming is indisputable. Several studies have suggested that temperature plays a crucial role in shaping both the abundance and composition of bacterial communities, thereby influencing plant productivity. , In laboratory conditions, the length of incubation time also affects the structure of bacterial communities in the culture medium. Contrary to common belief that rare and difficult-to-cultivate bacterial species grow slowly and increase after a prolonged incubation, studies have shown that not all bacteria require extended preincubation times to grow .…”
Section: New Strategies For Culturomicsmentioning
confidence: 99%